2020
DOI: 10.1002/jum.15299
|View full text |Cite
|
Sign up to set email alerts
|

Superb Microvascular Imaging Improves Detection of Vascularity in Indeterminate Renal Masses

Abstract: Objectives-Vascular assessment of indeterminate renal masses (iRMs) remains a crucial element of diagnostic imaging, as the presence of blood flow within renal lesions suggests malignancy. We compared the utility of Superb Microvascular Imaging (SMI; Canon Medical Systems, Tustin, CA), a novel Doppler technique, to standard color Doppler imaging (CDI) and power Doppler imaging (PDI) for the detection of vascularity within iRMs. Methods-Patients undergoing contrast-enhanced ultrasound (CEUS) evaluations for iRM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…This algorithm separates low-velocity flow signals from clutter artifacts and provides high sensitivity for the visualization of low-velocity flow with high resolution [ 16 ]. Investigators have reported that SMI can detect more flow signals within tumors than conventional color Doppler or PDUS and thereby complement conventional Doppler scans in the examination of tumorous lesions [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…This algorithm separates low-velocity flow signals from clutter artifacts and provides high sensitivity for the visualization of low-velocity flow with high resolution [ 16 ]. Investigators have reported that SMI can detect more flow signals within tumors than conventional color Doppler or PDUS and thereby complement conventional Doppler scans in the examination of tumorous lesions [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, as it is still unknown whether mSMI could effectively distinguish renal malignant tumor and benign renal mass in HD patients as well as nondialysis patients, accumulation of data will be needed to address this point. It has been reported that mSMI had the 63% sensitivity to detect indeterminate renal masses compared with other modalities such as color Doppler imaging or power Doppler imaging in nondialysis patients 6 . In addition, it will need further investigation with a large number of subjects about the sensitivity and specificity of mSMI of ultrasonography for detection of early stage RCCs in HD patients.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that mSMI had the 63% sensitivity to detect indeterminate renal masses compared with other modalities such as color Doppler imaging or power Doppler imaging in nondialysis patients. 6 In addition, it will need further investigation with a large number of subjects about the sensitivity and specificity of mSMI of ultrasonography for detection of early stage RCCs in HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Leong et al recently imaged 41 patients harboring 50 renal masses with Superb Micro-Vascular Imaging (SMI). They found that SMI had a higher diagnostic accuracy than standard color Doppler imaging and power Doppler imaging for the detection of vascularity within solid renal masses [47]. They concluded that SMI might have potential in the detection of microvascularity within indeterminate solid renal masses.…”
Section: Micro-doppler Techniquesmentioning
confidence: 99%